Sistem Noken Papua: Manifestasi Demokrasi Berbasis Kearifan Lokal - Nelwan Ronsumbre (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
The noken system, particularly related to the model of electoral balloting in Papua Province, has become an eternal topic that has been discussed and debated. The main point of the discussion is at least two aspects, namely the implementation of the noken system which is considered as local wisdom and the manifestation of deliberative democracy and in other parts that the system is considered to violate the principles of freedom and political rights of citizens. This research is a qualitative research with three research objects, namely the electoral system, deliberative democracy and political rights of citizens. This research shows that the implementation of noken in Papua is legitimate in the legal term and culturally the practice of the system is inseparable part of local wisdom and the manifestation of deliberative democracy. This study recommends the need for adjustments between the election noken system and the principles of justice, freedom and political rights of citizens through synchronization and harmonization of legal products regarding the noken system with protection of human rights in addition to the need to make incremental improvements to the system.